Innovating in Practice Perspectives and Experiences - Russo-Spena, Tiziana; Mele, Cristina; Nuutinen, Maaria (Springer International Publishing : Imprint: Springer, 2017)
XV, 529 p. 44 illus., 31 illus. in color.